Tris-EDTA no teste de sensibilidade antimicrobiana in vitro em amostras de Pseudomonas aeruginosa - Tanaka, E.M. [UNESP]; Ribeiro, M.G. [UNESP]; Megid, Jane [UNESP]; Listoni, F.J.P. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2002)
In vitro antimicrobial susceptibility of strains of Pseudomonas aeruginosa by standard diffusion disk test and a modified method, by the addition Tris-EDTA, was evaluated. Increase in sensitivity of agent using modified method was observed mainly in aminoglycosides (amikacin, gentamicin, tobramycin), quinolones (ofloxacin and norfloxacin) and cephalosporins (cefoperazone and ceftazidime) groups. by standard diffusion disk test and a modified method, by the addition Tris-EDTA, was evaluated. Increase in sensitivity of agent using modified method was observed mainly in aminoglycosides (amikacin, gentamicin, tobramycin), quinolones (ofloxacin and norfloxacin) and cephalosporins (cefoperazone and ceftazidime) groups.
In vitro antimicrobial sensitivity test with EDTA-Tris in strains of Pseudomonas aeruginosa
Keywords: Pseudomonas aeruginosa; sensibilidade antimicrobiana; Tris-EDTA; Pseudomonas aeruginosa; antimicrobial susceptibility test; Tris-EDTA; multiple drug resistance